Pelatihan Perancangan Desain Motif Scarf pada Pelaku Usaha di Kota Bandung - Almira, Rahmania; Surahman, Adi (LPPM ITEBA, 2024)
This fashion trend has led to the emergence of new entrepreneurs marketing scarves with various motifs. New businesses starting out use motifs found on the internet as the patterns applied to their products. This Community Service activity aims to enhance the abilities of entrepreneurs in building their brand and innovating their products. The activity is conducted for three participants and takes place at Marka Café in Bandung. The methods employed include surveys, analysis, lectures, discussions, Q&A sessions, and training. The training results in an increase in participants' knowledge and skills in building a brand, as well as improving their ability to innovate in the design motifs applied to scarves. Through the training on designing scarf motifs, entrepreneurs gain a deeper insight into building a brand, discovering the identity and uniqueness of their products through motif design. Additionally, participants are able to develop creativity and innovation in designing motifs.